2007
DOI: 10.1002/j.0022-0337.2007.71.5.tb04321.x
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Opinions About Treating Vulnerable Populations Immediately After Completing Community‐Based Clinical Experiences

Abstract: The purpose of this study was to analyze students' perceptions of comfort and anticipated willingness to treat selected special needs and traditionally underserved populations immediately upon completion of community-based clinical assignments. The sample consisted of University of Iowa senior dental students who completed a questionnaire that asked, in part, about student comfort with and future willingness to treat twelve vulnerable population groups. With student comfort and future willingness to treat each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 24 publications
7
61
1
Order By: Relevance
“…Thus, while the programme seemed to be able to help improve students' reactions to people with special healthcare needs, it proved unable to lower the barrier when it comes to treating them. This contrasts with results of previous studies with dental students as well as with practicing dentists which revealed a positive association between the exposure to education in the treatment of persons with special healthcare needs and the willingness to treat this clientele (see Introduction). A possible explanation for this discrepancy as well as for the increasing endorsement of specialised services may be sought in students' growing awareness that they were insufficiently prepared for treating this clientele.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, while the programme seemed to be able to help improve students' reactions to people with special healthcare needs, it proved unable to lower the barrier when it comes to treating them. This contrasts with results of previous studies with dental students as well as with practicing dentists which revealed a positive association between the exposure to education in the treatment of persons with special healthcare needs and the willingness to treat this clientele (see Introduction). A possible explanation for this discrepancy as well as for the increasing endorsement of specialised services may be sought in students' growing awareness that they were insufficiently prepared for treating this clientele.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, several studies have shown that dentists who had undergone training in managing patients with special healthcare needs and who perceived their educational experiences as valuable felt more comfortable with treating this group of patients and treated more of these patients compared to those not exposed to this kind of training . Similarly, students who perceived themselves prepared for the treatment of patients with special needs showed greater future intention to treat this clientele …”
Section: Introductionmentioning
confidence: 99%
“…However, even for the White and non-White comparison in the costs scale, the p-value was 0.0139 which can be considered significant at a=0.05 level but would not be considered significant after Bonferroni adjustment for multiple comparisons. This finding is consistent with Holtzman et al's study and Kuthy et al's study which did not find significant differences in students' attitudes by age, gender, or volunteer experience (Holtzman & Seirawan, 2009) (Kuthy et al, 2007).…”
Section: Relationship Between Student Characteristics and Attitudesupporting
confidence: 91%
“…The authors suggested that access to oral health care for underserved patients could potentially be increased if dental students were more overtly educated about the importance of treating patients from all segments of society (Smith et al, 2006). year from dental school, and community assignments influence only a few of these targeted population groups (Kuthy, Heller, Riniker, McQuistan, & Qian, 2007). (details about this program was described in the earlier section of this chapter) is successful in stimulating reform in U.S. dental schools in terms of engaging more in community-based dental education, future students will develop greater awareness regarding critical access problems and the competencies required to effectively care for diverse populations (P. L. Davidson et al, 2007).…”
Section: Attitudementioning
confidence: 99%
“…A viable clinical option is to integrate HIV-specific community-based clinical experiences into the dental curriculum. Kuthy et al [31],found this strategy to be helpful in increasing dental students' willingness to treat a variety of underserved populations, including people infected with HIV/AIDS.…”
Section: Discussion:-mentioning
confidence: 99%